Significações e ressignificações do patrimônio cultural: as fazendas históricas e o turismo nos Campos Gerais do Paraná - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2007)
The activity of cattle driving (tropeirsimo) has been a historical marker in the history of Brazil throughout the 18th and 19th century resulting in the effective integration of the South into the whole of the country. Thus, the Campos Gerais region has become an important element in the country’s structure. Cattle driving has left us an important historical-cultural legacy both in material and non-material forms. The herdsmen of the old times had developed a very specific way of life – in language, nutritional behavior and clothing. Chapels and ranches have been constructed along their trails. Today, the roads once used by the herdsmen and their living spaces represent an important historical moment which can be re-signified both by the local population and by tourists coming from near and far to visit this legacy. The main target of this research is to reflect critically on processes of signification and re-signification in relation to this heritage under the influence of tourism. For this purpose, vast theoretical and regional bibliographical material has been evaluated, and extensive field work has been performed. The analysis refers primarily to the architectural heritage of the old ranches (fazendas) of the Campos Gerais region involved in the cattle driving process, especially to those which have passed a process of re-signification acquiring a new language under the influence of tourism. These processes of re-signification appear in different forms on the ranches, ranging from visits to farm houses with preserved furniture and decorations, participation in walking and riding trails along the old roads, experiencing the fazenda life of the old days, with traditional dishes, story telling and memories, at the campfire and with chimarrão (mate tea), up to the use of documentaries and folklore presentations. In 2003, a specific tourist project, the “Rota dos Tropeiros” (=The cattle driving trail), has been launched in Paraná to coordinate different tourist attractions based on its regional character and reinforcing the re-signification process of the tropeirismo. The activity of cattle driving (tropeirsimo) has been a historical marker in the history of Brazil throughout the 18th and 19th century resulting in the effective integration of the South into the whole of the country. Thus, the Campos Gerais region has become an important element in the country’s structure. Cattle driving has left us an important historical-cultural legacy both in material and non-material forms. The herdsmen of the old times had developed a very specific way of life – in language, nutritional behavior and clothing. Chapels and ranches have been constructed along their trails. Today, the roads once used by the herdsmen and their living spaces represent an important historical moment which can be re-signified both by the local population and by tourists coming from near and far to visit this legacy. The main target of this research is to reflect critically on processes of signification and re-signification in relation to this heritage under the influence of tourism. For this purpose, vast theoretical and regional bibliographical material has been evaluated, and extensive field work has been performed. The analysis refers primarily to the architectural heritage of the old ranches (fazendas) of the Campos Gerais region involved in the cattle driving process, especially to those which have passed a process of re-signification acquiring a new language under the influence of tourism. These processes of re-signification appear in different forms on the ranches, ranging from visits to farm houses with preserved furniture and decorations, participation in walking and riding trails along the old roads, experiencing the fazenda life of the old days, with traditional dishes, story telling and memories, at the campfire and with chimarrão (mate tea), up to the use of documentaries and folklore presentations. In 2003, a specific tourist project, the “Rota dos Tropeiros” (=The cattle driving trail), has been launched in Paraná to coordinate different tourist attractions based on its regional character and reinforcing the re-signification process of the tropeirismo.
Signification and re-signification of cultural heritage: the historical ranches (fazendas) of the Campos Gerais region in Southern Brazil and tourism
Keywords: ressignificação cultural; tropeirismo; fazendas históricas; Campos Gerais (PR); turismo; re-signification; culture; cattle driving; tropeirismo; historical ranches; fazendas; Campos Gerais (PR); tourism.; CNPQ::CIENCIAS SOCIAIS APLICADAS